2022
DOI: 10.1037/xlm0001120
|View full text |Cite
|
Sign up to set email alerts
|

Nymph piss and gravy orgies: Local and global contrast effects in relational humor.

Abstract: How does the relation between two words create humor? In this article, we investigated the effect of global and local contrast on the humor of word pairs. We capitalized on the existence of psycholinguistic lexical norms by examining violations of expectations set up by typical patterns of English usage (global contrast) and within the local context of the words within the word pairs (local contrast). Global contrast was operationalized as lexical-semantic norms for single-words and local contrast was operatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The average humor rating for these words are in parentheses, based on a Likert scale ranging from 1 (least humorous) to 5 (most humorous). These humor norms have proven to be useful in helping language scientists make some inroads into understanding the perception of humor in words and language (Siew et al, 2022;Westbury & Hollis, 2019. Engelthaler and Hills (2018) correlated humor norms with various lexical-semantic word norms and found that word humor was most strongly correlated with inverse word frequency (-0.42 with frequencies from the British National Corpus).…”
Section: Psycholinguistic Research On Dialectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average humor rating for these words are in parentheses, based on a Likert scale ranging from 1 (least humorous) to 5 (most humorous). These humor norms have proven to be useful in helping language scientists make some inroads into understanding the perception of humor in words and language (Siew et al, 2022;Westbury & Hollis, 2019. Engelthaler and Hills (2018) correlated humor norms with various lexical-semantic word norms and found that word humor was most strongly correlated with inverse word frequency (-0.42 with frequencies from the British National Corpus).…”
Section: Psycholinguistic Research On Dialectsmentioning
confidence: 99%
“…Westbury et al (2016)'s analysis of nonwords found that nonwords with lower entropy (which quantified greater incongruity between expectation and what was observed in the letter sequences, i.e., an "unlikely" nonword) were considered to be funnier than nonwords with higher entropy (e.g., the nonword "suppopp" is funnier than "tessina"). Siew et al (2022)'s analysis of word pair humor found that word pairs containing words with high phonological similarity and low semantic similarity (i.e., high levels of local violations of word co-occurrence expectations within a two-word context) were considered to be funnier as compared to word pairs containing words of low phonological similarity and high semantic similarity (e.g., the word pair "stripper hippo" is funnier than "conserve health"). In both of these examples as well as the current study, humor appears to involve the computation of expectations given one's linguistic experience (whether it is with sequences of letters or words or global frequency of words), coupled with an evaluation of whether expectations are violated.…”
Section: Implications For Humor Researchmentioning
confidence: 99%
“…A cognitive system with similar abilities could create novel nodes, such as the concept of cabbage cage or gravy orgy , which also represent the kind of novel high‐entropy stimuli associated with humor (Siew, Engelthaler, & Hills, under review). Moreover, if as network scientists we want to imagine that the nodes in our networks represent constellations of neural activity in a brain, then we must accept that cabbages , cages , and cabbage cages all represent different patterns of activity across a distributed representation (Musz & Thompson‐Schill, 2015).…”
Section: Alternative Cognitive Network Metaphorsmentioning
confidence: 99%